Assessment of horse owners' ability to recognise equine laminitis: A cross‐sectional study of 93 veterinary diagnosed cases in Great Britain. (3rd July 2017) - Pollard, D.; Wylie, C. E.; Verheyen, K. L. P.; Newton, J. R.
Summary: Background: Use of owner‐reported data could further epidemiological knowledge of equine laminitis. However, owner recognition of laminitis has not previously been assessed. Objectives: The primary objective was to establish whether cases of owner‐suspected laminitis would be confirmed as laminitis by the attending veterinary surgeon. Secondary objectives were to compare owner‐ and veterinary‐reported information from veterinary‐confirmed cases of equine laminitis. Study design: Cross‐sectional study. Methods: Twenty‐five British veterinary practices were invited to submit laminitis reporting forms (LRFs) for active laminitis cases attended between January 2014 and October 2015; detailing 27 clinical signs, 5 underlying conditions and 7 risk factors associated with laminitis. Owners were invited to independently complete a modified LRF if reason for the veterinary visit was suspicion of laminitis. Differences between paired veterinary and owner LRFs, and between cases where owners did and did not recognise laminitis, were assessed using McNemar's and Fisher's Exact tests, respectively. Results: Veterinary LRFs were received for 93 veterinary‐diagnosed laminitis cases. All 51 owner‐suspected cases were confirmed by veterinary diagnosis, with the remaining 42 (45.2%) not recognised as laminitis by owners. Undefined lameness, foot abscesses, colic and stiffness were common reasons for owner‐requested veterinary visits in owner‐unrecognised cases. 'Divergent growth rings' (prevalence difference: +27.3%, P = 0.01) and 'breed type' (prevalence difference: +21.2%, P = 0.04) were more commonly reported by veterinary surgeons in owner‐recognised compared to owner‐unrecognised cases. 'Difficulty turning', 'shifting weight' and risk factor 'body condition' were more frequently reported by veterinary surgeons whilst 'increased hoof temperature' was reported more frequently by owners. Main limitations: The limited clinical data restricted statistical inferences regarding the secondary objectives. Conclusions: All owner‐suspected laminitis cases were confirmed upon veterinary examination, showing validity for the inclusion of owner‐reported cases in future epidemiological studies. However, failure of laminitis recognition by owners highlights further need for evidence‐based education to ensure early disease detection.